Academic–Correctional Health Partnerships: Preparing the Correctional Health Workforce for the Changing Landscape—Focus Group Research Results. (January 2015) - Hale, Janet Fraser; Haley, Heather-Lyn; Jones, Judy L.; Brennan, Allyson; Brewer, Arthur
Providing health care in corrections is challenging. Attracting clinicians can be equally challenging. The future holds a shortage of nurses and primary care physicians. We have a unique opportunity, now, to develop and stabilize our workforce, create a positive image, and enhance quality before the health care landscape changes even more dramatically. Focus groups were conducted with 22 correctional health care professionals divided into three groups: physicians (6), nurses (4), and nurse practitioners/physician assistants (12). Content focused on curricular themes, but additional themes emerged related to recruitment and retention. This article describes recruitment challenges, strategic themes identified, and the proposed initiatives to support a stable, high-quality correctional health workforce.